Online Collaborative Learning For Malaysian Secondary Schools: A Case Study Of Geometry - Koo, Ah Choo (2006)
This study aims to explore and investigate the factors affecting students' and teachers' perceived readiness for online collaborative learning (OCL) in Malaysian secondary schools, especially for teaching and learning geometry. This thesis consists of a compilation of two studies related to OCL. The first is a case study on OCL which was participated by a sample of 32 secondary school students and 5 teachers. This study is inclined towards qualitative research technique. The second study uses quantitative research technique through questionnaire survey to investigate the opinions of the teachers and students on OCL and geometry education.